Antifungal Potency of Musa paradisiaca L. Peel Extract Against Candida albicans as Acrylic Denture Cleanser - Nada Fathiyyah; Ivony Fitria; Eni Rahmi; Desy Purnama Sari; Gunawan (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2025)
Background: Denture stomatitis is one of the diseases that can arise due to unattended denture hygiene. One of the microorganisms that cause denture stomatitis is Candida albicans. Objective: The purpose of this study is to determine the potential of Musa paradisiaca L. extract concentrations of 25;50;75% as antifungal against Candida albicans on removable denture acrylic base. Materials and Methods: This study is a laboratory experimental study with a post-test-only control group design using 28 samples for 4 treatment groups. Candida albicans (ATCC 10231) was bred on acrylic plates. The acrylic samples were immersed in aquadest, Musa paradisiaca L. peel extract concentrations of 25;50; and 75%, respectively. The sample was immersed for 10 minutes and the amount of Candida albicans was calculated using colony counter. The research data was analyzed with the One-Way Anova parametric test followed by a post-hoc LSD test. Results: Based on the results of statistical tests, significant differences (p<0.05) were obtained in Musa paradisiaca L. peel extract concentrations of 25; 50; and 75% compared to the control group. There was a decrease in the amount of Candida albicans in the three concentrations of Musa paradisiaca L. peel extract, with increased effectiveness at a concentration of 75%. Conclusion: Musa paradisiaca L. peel extract 25; 50; and 75% solution, especially at 75% concentration, has antifungal activity to reduce the number of Candida albicans and has the potential as an acrylic denture cleaner.